Molecular Networking to Screen Macroalgal Secondary Metabolites: Case for West Timor Macroalgae - Turupadang, Welem; Johanis, Marskel (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
The research describes how molecular networking was used as a screening tool to prioritize the isolation workflow of 40 macroalgae sampled from West Timor waters, Indonesia, in addition to a Nuclear Magnetic Resonance-based (NMR) spectroscopy strategy. A mass spectrometry (MS) was employed to generate spectra that later be used as data to produce the molecular network with the Global Natural Product Social Molecular Networking (GNPS) website. The screening process used the molecular network, which assisted in the selection of six samples of macroalgae out of the 40 samples for further examination. Lastly, an NMR-based protocol was employed to choose the samples of interest to be investigated further. Six samples were shortlisted from the GNPS molecular network based on specimens, which were then validated with 1H NMR spectroscopy to finally prioritized three samples.